2018
DOI: 10.1016/j.aller.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Resources to handle childhood asthma in Spain: The role of plans and guides and the participation of nurses

Abstract: The availability of asthma plans/guidelines and resources for diagnosis and follow-up is not sufficient to improve important aspects of primary care for children with asthma. Organisational changes are necessary to include programmed asthma-related visits and paediatric teams with greater involvement of the nurses when caring for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…The education given by nurses to pediatric patients improved the inhalation technique, achieving better control of the disease and use of the health system. These results confirmed that educational interventions performed by a pediatric nurse following demonstrations and face-to-face training sessions help achieve quality standards in inhalation therapy and, in turn, support the preliminary work performed at other care levels, such as primary care pediatric consultations [ 18 ]. The meta-analysis performed by Kuethe et al, recorded in the Cochrane database, confirmed that nurses could properly take on the management and review of patients with well-controlled asthma [ 19 ].…”
Section: Discussionsupporting
confidence: 65%
“…The education given by nurses to pediatric patients improved the inhalation technique, achieving better control of the disease and use of the health system. These results confirmed that educational interventions performed by a pediatric nurse following demonstrations and face-to-face training sessions help achieve quality standards in inhalation therapy and, in turn, support the preliminary work performed at other care levels, such as primary care pediatric consultations [ 18 ]. The meta-analysis performed by Kuethe et al, recorded in the Cochrane database, confirmed that nurses could properly take on the management and review of patients with well-controlled asthma [ 19 ].…”
Section: Discussionsupporting
confidence: 65%